Beyond full jurisdiction: pathology and inter-professional relations in precision medicine. Issue 1 (2nd January 2021) - Bergeron, Henri; Castel, Patrick; Vézian, Audrey
Abstract : The rise of precision medicine represents a challenge for pathology, which must now more closely link research and diagnostic and collaborate on new bases with other specialties. Our paper is based on the study of four French cancer centers invested in developing precision medicine. Molecular biology is particularly threatening for pathologists in settings where medical oncologists and biologists believe that the discipline is capable of presiding over if not altogether replacing morphology as the principal basis for diagnosis. However, we will show that the organizational arrangements for circulating tumor specimens and producing diagnoses, as well as the place occupied by pathologists in these arrangements, have varied from place to place and over time. These configurations are the result of preexisting arrangements and local negotiations among professionals, where the aim is rather to include and coordinate specialties within the production line rather than exclude them from the jurisdictional remit.